1984
DOI: 10.1144/gsl.qjeg.1984.017.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Controls on contaminant migration at the Villa Farm Lagoons

Abstract: Summary The disposal of liquid wastes containing heavy metals and organic solvents into lagoons excavated to beneath the water table in a shallow, unconsolidated sand aquifer has resulted in local groundwater pollution. The development of the pollution plume appears to be controlled by the morphology of the aquifer, the distribution of permeability within it and the head distribution in the vicinity of the lagoons. On the basis of redox reactions three geochemical zones have been identified down hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 1 publication
3
5
0
Order By: Relevance
“…These confirm the overall picture described by Williams et al (1984) but show that since waste dumping has ceased there has been a general dilution of the plume, as the plume itself has spread (Williams et al, 1995). In particular, maximum chloride concentrations close to the lagoons fell from >4000 to 600 mg L" 1 .…”
Section: Groundwater Chemistrysupporting
confidence: 72%
See 3 more Smart Citations
“…These confirm the overall picture described by Williams et al (1984) but show that since waste dumping has ceased there has been a general dilution of the plume, as the plume itself has spread (Williams et al, 1995). In particular, maximum chloride concentrations close to the lagoons fell from >4000 to 600 mg L" 1 .…”
Section: Groundwater Chemistrysupporting
confidence: 72%
“…A strong brown coloration is due to the presence of iron oxyhydroxides. Clays, mainly kaolinite and illite, can constitute up to 15% of the bulk mineralogy (Williams et al, 1984).…”
Section: Geology and Hydrogeologymentioning
confidence: 99%
See 2 more Smart Citations
“…Christensen et al, 1992). This reducing environment has been shown to be important in controlling the transport and fate of some organic compounds with otherwise high attenuation potential (Williams et al, 1984;Holm et al, 1995). For sources of contamination from septic tanks it has also been suggested that a redox-mediated persistence of EOCs is important controlling factor (Carrara et al, 2007).…”
Section: Biodegradation and Redox Controlsmentioning
confidence: 99%